Developments in Agricultural Soil Quality and Health: Reflections by the Research Committee on Soil Organic Matter Management - Wander, Michelle M.; Cihacek, Larry J.; Coyne, Mark; Drijber, Rhae A.; Grossman, Julie M.; Gutknecht, Jessica L. M.; Horwath, William R.; Jagadamma, Sindhu; Olk, Daniel C.; Ruark, Matt; Snapp, Sieglinde S.; Tiemann, Lisa K.; et al. (Frontiers in Environmental Science, 2019)
The North Central Education and Research Activity Committee (NCERA-59) was formed in 1952 to address how soil organic matter formation and management practices affect soil structure and productivity. It is in this capacity that we comment on the science supporting soil quality and associated soil health assessment for agricultural lands with the goal of hastening progress in this important field. Even though the suite of soil quality indicators being applied by U.S. soil health efforts closely mirrors the ‘minimum data set’ we developed and recommended in the mid-1990s, we question whether the methods or means for their selection and development are sufficient to meet current and emerging soil health challenges. The rush to enshrine a standard suite of dated measures may be incompatible with longer-term goals. Legitimate study of soil health considers soil change accrued over years to decades that influence on- and off-site function. Tailoring of methods to local conditions is needed to effectively apply and interpret indicators for different soil resource regions and land uses. Adherence to a set suite of methods selected by subjective criteria should be avoided, particularly when we do not yet have adequate data or agreed upon interpretive frameworks for many so-called ‘Tier 1’ biological indicators used in soil health assessment. While pooling data collected by producer-groups is one of the most exciting new trends in soil health, standardizing methods to meet broad inventory goals could compromise indicator use for site or application-specific problem solving. Changes in our nation’s research landscape are shifting responsibility